Hate speech in Asia and Europe : beyond hate and fear - Kang, Myŏng-gu, 1953-; Rivé-Lasan, Marie-Orange, 1966-; Kim, U-ja; Hall, Philippa; Pak, So-jŏng, 1990- (Routledge contemporary Asia series., 2020)
'This edited collection provides a timely review of the current state of hate speech research in Asia and Europe, through the comparative examples of Korea, Japan and France. Extending the study of hate speech studies beyond the largely western emphasis on European and US contexts dominant in the field, this book's comparative framework aims to examine hate speech as a global phenomenon spanning Asian and European contexts. An innovative range of nuanced empirical case studies explore hate speech by analyzing gendered hate speech and nationality, French cartoon humour, official counter radicalization narratives and the use of international law to inform domestic legislation in the Philippines and Japan. A fresh perspective on Asian and European hate speech, this book's evaluation of current of hate speech research also identifies future directions for the development of theory and method. Filling a critical gap in the literature, Hate Speech in Asia and Europe will appeal to students and scholars of law, politics, religion, history, social policy and social science more broadly, as well as Asian Studies."--